2018
DOI: 10.1136/bjsports-2018-099773
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exercise is not associated with fetal mortality: a systematic review and meta-analysis

Abstract: ObjectiveTo perform a systematic review of the relationship between prenatal exercise and fetal or newborn death.DesignSystematic review with random-effects meta-analysis and meta-regression.Data sourcesOnline databases were searched up to 6 January 2017.Study eligibility criteriaStudies of all designs were included (except case studies) if they were published in English, Spanish or French and contained information on the population (pregnant women without contraindication to exercise), intervention (subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 69 publications
3
42
0
1
Order By: Relevance
“…Fear of miscarriage can be a barrier to prenatal exercise in early pregnancy 121 ; however, a recent meta-analysis demonstrated no increased odds of miscarriage or perinatal mortality in otherwise healthy pregnant women who exercised compared with those who did not. 18 It should be noted that this included spontaneous miscarriage data, and not specifically, recurrent pregnancy loss. Regardless, it remains unclear as to how exercise would negatively influence factors that lead to recurrent pregnancy loss.…”
Section: Recurrent Miscarriage and Pregnancy Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Fear of miscarriage can be a barrier to prenatal exercise in early pregnancy 121 ; however, a recent meta-analysis demonstrated no increased odds of miscarriage or perinatal mortality in otherwise healthy pregnant women who exercised compared with those who did not. 18 It should be noted that this included spontaneous miscarriage data, and not specifically, recurrent pregnancy loss. Regardless, it remains unclear as to how exercise would negatively influence factors that lead to recurrent pregnancy loss.…”
Section: Recurrent Miscarriage and Pregnancy Lossmentioning
confidence: 99%
“…17 Critically, these benefits occur without increasing the risk of having a small baby, preterm birth or a miscarriage. 18 Despite these known benefits of physical activity on maternal and fetal health, there remains a subset of women who are advised against exercise due to a variety of preexisting or pregnancy-specific conditions, known as contraindications.…”
Section: Introductionmentioning
confidence: 99%
“…> 4000 g, 39% decreased odds) (Davenport et al, 2018b). The safety of prenatal PA has been confirmed as no increased odds of preterm birth, altered fetal growth (Davenport et al, 2018b), miscarriage (Davenport et al, 2019a) or cesarean section (Davenport et al, 2019b) have been reported. According to the 2019 Canadian Guideline for Physical Activity throughout Pregnancy, pregnant women without contraindications to PA should accumulate at least 150 min per week of moderate-intensity physical activity (MPA) (Mottola et al, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…As evidências disponíveis mostram que a prática de atividade física durante a gestação é segura e não apresenta riscos para o desenvolvimento fetal e saúde da criança (Quadro 3). Evidências de qualidade baixa apontam que a prática de atividade física durante a gestação não aumenta o risco de abortos, anomalias congênitas, mortalidade prematura 18 , ruptura da bolsa amniótica antes do início do trabalho de parto, cesariana, indução do trabalho de parto, tempo de parto, laceração do períneo, fadiga, lesão, trauma musculoesquelético e danos maternos, mesmo quando praticada no primeiro trimestre 19 . Também há evidências de qualidade baixa Quadro 2 -Resumo de evidências do efeito da atividade física sobre a saúde da mulher.…”
Section: Atividade Física Durante a Gestação Parto Desenvolvimento Fetal E Saúde Do Bebêunclassified